Interferon Regulatory Factor 5 Controls Necrotic Core Formation in Atherosclerotic Lesions by Impairing Efferocytosis. Issue 12 (19th September 2017) - Seneviratne, Anusha N.; Edsfeldt, Andreas; Cole, Jennifer E.; Kassiteridi, Christina; Swart, Maarten; Park, Inhye; Green, Patricia; Khoyratty, Tariq; Saliba, David; Goddard, Michael E.; Sansom, Stephen N.; Goncalves, Isabel; et al.
Abstract : Background: Myeloid cells are central to atherosclerotic lesion development and vulnerable plaque formation. Impaired ability of arterial phagocytes to uptake apoptotic cells (efferocytosis) promotes lesion growth and establishment of a necrotic core. The transcription factor interferon regulatory factor (IRF)-5 is an important modulator of myeloid function and programming. We sought to investigate whether IRF5 affects the formation and phenotype of atherosclerotic lesions. Methods: We investigated the role of IRF5 in atherosclerosis in 2 complementary models. First, atherosclerotic lesion development in hyperlipidemic apolipoprotein E-deficient (ApoE -/- ) mice and ApoE -/- mice with a genetic deletion of IRF5 (ApoE -/- Irf5 -/- ) was compared and then lesion development was assessed in a model of shear stress-modulated vulnerable plaque formation. Results: Both lesion and necrotic core size were significantly reduced in ApoE -/- Irf5 -/- mice compared with IRF5-competent ApoE -/- mice. Necrotic core size was also reduced in the model of shear stress-modulated vulnerable plaque formation. A significant loss of CD11c + macrophages was evident in ApoE -/- Irf5 -/- mice in the aorta, draining lymph nodes, and bone marrow cell cultures, indicating that IRF5 maintains CD11c + macrophages in atherosclerosis. Moreover, we revealed that the CD11c gene is a direct target of IRF5 in macrophages. In the absence of IRF5, CD11c - macrophages displayed a significant increase in expression of the efferocytosis-regulating integrin-β3 and its ligand milk fat globule-epidermal growth factor 8 protein and enhanced efferocytosis in vitro and in situ. Conclusions: IRF5 is detrimental in atherosclerosis by promoting the maintenance of proinflammatory CD11c + macrophages within lesions and controlling the expansion of the necrotic core by impairing efferocytosis. Abstract : Supplemental Digital Content is available in the text.